Direct numerical simulation of two-phase pipe flow: Influence of the domain length on the flow regime. (November 2021) - Plana, Carlos; Song, Baofang; Avila, Marc
Abstract: We investigate the dynamics of a kerosene–water mixture in a vertical pipe flow by solving the Cahn–Hilliard–Navier–Stokes equations. We compute the linear stability of laminar core-annular flow in a vertical pipe and find that it is highly unstable. By performing direct numerical simulations initialized with a slightly perturbed core-annular flow, we show that the system transitions to turbulence and finally relaxes into a turbulent slug flow regime provided that the pipe is sufficiently long. This configuration presents mild turbulence and large scale three-dimensional recirculation patterns. Our work highlights the need for applying nonlinear-dynamics approaches and carefully selecting the domain length to investigate the patterns observed in two-phase pipe flows and demonstrates the capabilities of phase-field methods to reliably simulate flows under realistic experimental conditions. Highlights: Simulation of kerosene–water pipe flow using phase-field method. Slug flow configuration stable; water drops stable in isolation. Chaotic recirculation patterns inside the slug structures. Turbulence intensity sensitive to interface thickness; flow patterns unchanged.